FDI spillover effects on innovation activities of knowledge-using and knowledge-creating firms: Evidence from an emerging economy - Nina Vujanović; Iraj Hoshi; Mehtap Hisarciklilar; Slavo Radošević; Nebojša Stojčić (The Vienna Institute for International Economic Studies (wiiw), 2022)
The beneficial effects of innovation for firms' performance and competitiveness are well documented, but it has been suggested in recent years that innovation regimes differ between advanced and emerging economies. While advanced economies rely on knowledge generation, their emerging counterparts follow mainly a knowledge-use regime through the application of existing knowledge and technology. Climbing up the technological ladder can be helped through spillovers from foreign investors to local firms. We investigate whether FDI spillovers influence different phases of the innovation process (from decision to innovate to productivity) among knowledge-using and knowledge-creating firms in an emerging European economy. The results show that the innovation process in emerging economies is closer to the imitation than the creation of novel products. Local firms benefit from foreign counterparts in the early phase of the innovation process. Stronger FDI effects are found among firms that undertake innovation through knowledge use rather than through knowledge generation.
Keywords: F21; F23; L25; C31; L21; 330; knowledge use; knowledge generation; FDI; innovation; emerging economy